Persepi Tentang Pembelajaran Daring Pendidikan Jasmani Olahraga Dan Kesehatan Pada Siswa Kelas VIII SMP Negeri 92 Jakarta - Tirta Ramadhani, Nadia Sectio; Tahki, Kurnia; Sukriadi, Slamet (Jurnal Speed (Sport, Physical Education, Empowerment), 2023)
ABSTRACT In this study, the goal to be achieved by the researcher is to find out how the perception of class VIII students towards online learning of Physical Education, Sports and Health at SMP Negeri 92 Jakarta is. This research is a quantitative descriptive study with a survey method. The population in this study were all students of class VIII SMP Negeri 92 Jakarta, totaling 320 students. The sample size of this study was grade VIII students at SMP Negeri 92 Jakarta, totaling 111 students.sampling technique used was random sampling by means of lottery, which consisted of 8 classes, namely class VIIIA to VIIIH. Data were collected by questionnaire. Data analysis was carried out by descriptive statistical analysis with percentages. Based on the results of research that has been obtained by data analysis, it can be concluded that the perception of class VIII students from the subject amounting to 111 students. The results of this study indicate that the perception of class VIII SMP Negeri 92 is categorized as good, judging from the percentage table of 111 students there are 22 students in good category with a percentage of 19.8%, 72 students in the category enough with a percentage of 64.9%%, 22 students in the moderate category with a percentage of 15.3%%, Keywords: Learning, Online, Physical Education,